1990
DOI: 10.1136/thx.45.5.373
|View full text |Cite
|
Sign up to set email alerts
|

Value of washings and brushings at fibreoptic bronchoscopy in the diagnosis of lung cancer.

Abstract: A retrospective study was performed to evaluate the diagnostic yield for lung cancer from histological biopsy specimens and from washings and brushings for cytological examination taken at fibreoptic bronchoscopy. The Any patient with an inadequate follow up (because of lost records, for example) or with insufficient data was excluded from the study.The two most common reasons for bronchoscopy were an abnormal chest radiograph (493 cases) and haemoptysis (104 cases). Other reasons for bronchoscopy included d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
86
5
13

Year Published

1996
1996
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(113 citation statements)
references
References 10 publications
9
86
5
13
Order By: Relevance
“…No entanto, o adenocarcinoma predominou no gru-Endoscopia respiratória em 89 pacientes com neoplasia pulmonar po 2, que foi de 27,7% contra 7,5% no grupo 1, enquanto o carcinoma indiferenciado de pequenas células predominou no grupo 1 com 13,2% e 5,5% no grupo 2. Esses dados concordam com vários autores (4,8,(19)(20)(21)(22)(23) , que em suas séries descrevem carcinomas epidermóides e indiferenciado de pequenas células como lesões visíveis à endoscopia por serem mais centrais. Já os adenocarcinomas, por ser mais periféricos (4,8,22) , não são visíveis à endoscopia ou se apresentam como sinais indiretos de tumor.…”
Section: Discussionunclassified
“…No entanto, o adenocarcinoma predominou no gru-Endoscopia respiratória em 89 pacientes com neoplasia pulmonar po 2, que foi de 27,7% contra 7,5% no grupo 1, enquanto o carcinoma indiferenciado de pequenas células predominou no grupo 1 com 13,2% e 5,5% no grupo 2. Esses dados concordam com vários autores (4,8,(19)(20)(21)(22)(23) , que em suas séries descrevem carcinomas epidermóides e indiferenciado de pequenas células como lesões visíveis à endoscopia por serem mais centrais. Já os adenocarcinomas, por ser mais periféricos (4,8,22) , não são visíveis à endoscopia ou se apresentam como sinais indiretos de tumor.…”
Section: Discussionunclassified
“…Naryshkin et al, who examined the reliability of bronchoscopic cytology in relation to biopsy, found a rate of 10.7% of nondiagnostic biopsies [23]. Some other studies have demonstrated diagnostic rates of 9.5% and 2.1% for bronchial washing (without histological confirmation), respectively [24,25]. We identified 54/678 (8.0%) cases in which only cytology was diagnostic or generated an abnormal result leading to further investigation.…”
Section: Discussionmentioning
confidence: 94%
“…While the diagnostic yield for washings in patients with endoscopically visible (central) tumors varies from 49 to 76% and is similar to the yield for brushings (52 to 77%) but is inferior to the yield of biopsies (71 to 91%); the efficacy of washings in patients with endoscopically nonvisible (peripheral) tumors, varies from 35 to 52% and is similar to the yield for brushings (26 to 52%) and for biopsies (36 to 61%). [11][12][13][14] Some studies have reported that adding bronchial washings to biopsies and brushings increases the diagnostic yield; whereas others, have reported no additional value of washings. 12,13,[17][18][19][20] In the present study, bronchial washing successfully detected lung carcinoma in a single patient alone, and a sensitivity as low as 3.4%, was obtained.…”
Section: Discussionmentioning
confidence: 99%